Muhammad - Weinberger, Eliot (London Verso, 2006)
A lyrical biography of the Prophet, composed from the words of Muslims throughout the centuries. This work weaves a prose poem, spanning Muhammad's birth and childhood; his adolescence, miracles and marriages; to the isra and miraj, his journey from Mecca to Jerusalem and ascent into heaven, with the angel Jibril (Gabriel) as his guide.
Keywords: Muslims -- Saudi Arabia -- Muḥammad, Prophet, -632